2016
DOI: 10.1016/j.jtcvs.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of mild aortic regurgitation in predicting mortality after transcatheter aortic valve replacement

Abstract: Even mild aortic regurgitation after transcatheter aortic valve replacement is associated with worse long-term mortality. There may be prognostic value in reporting milder categories of aortic regurgitation with more granular gradations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…It appears that residual AR (most often caused by perivalvular leak) blocks a decrease in LVEDV post‐TAVR. Postprocedural AR is known as a significant prognostic factor after TAVR . Several studies conducted with early generation valves showed that even mild AR has an adverse impact on survival .…”
Section: Discussionmentioning
confidence: 99%
“…It appears that residual AR (most often caused by perivalvular leak) blocks a decrease in LVEDV post‐TAVR. Postprocedural AR is known as a significant prognostic factor after TAVR . Several studies conducted with early generation valves showed that even mild AR has an adverse impact on survival .…”
Section: Discussionmentioning
confidence: 99%
“…Our initial literature search resulted in total of 3,447 articles. A total of 25 articles [3,[6][7][8][9][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] including total of 21,018 patients were finally included for quantitative synthesis (meta-analysis). Detailed study selection flow is summarized in Supporting Information 1.…”
Section: R Esu L Tsmentioning
confidence: 99%
“…Commercially available earlier-generation transcatheter valves, despite providing good clinical outcomes, were not free from shortcomings; indeed, high rates of conduction abnormalities, permanent pacemaker implantation (PPI) or vascular complications remained important issues to be addressed. More importantly, though, higher incidence of paravalvular leak (PVL), in turn associated with increased late mortality and higher rate of other adverse clinical incidents, as compared to SAVR [11][12][13], often outweigh the benefits of transcatheter approach.…”
Section: Introductionmentioning
confidence: 99%